2014
DOI: 10.1016/j.lingua.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The status of s in Dominican Spanish

Abstract: Theoretical linguistic treatments of the intrusive-s of popular Dominican Spanish (yo[s] tuve < yo tuve 'I had') assume the hypothesis that illiterate speakers have reanalyzed their phonologies so that lexical items no longer contain any trace of coda-s. As a consequence, illiterate speakers are said to restore an s into random syllable codas in an attempt to hypercorrect to a more elevated style. Using natural data gathered from sociolinguistic interviews with Dominicans of diverse literacy levels, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…It also tends to emerge in more formal situations (Morgan 1998). Additionally, voiceless stops (p, t, k) act as attractors for intrusive-s across word boundaries (Bullock et al 2014). Although semiliterate Dominican speakers seem to know where the /s/ belongs, they choose to express s-insertion for reasons of identity, social prestige, and discursive functions.…”
Section: Intrusive Coda /S/ Hypercorrection: Articulatory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It also tends to emerge in more formal situations (Morgan 1998). Additionally, voiceless stops (p, t, k) act as attractors for intrusive-s across word boundaries (Bullock et al 2014). Although semiliterate Dominican speakers seem to know where the /s/ belongs, they choose to express s-insertion for reasons of identity, social prestige, and discursive functions.…”
Section: Intrusive Coda /S/ Hypercorrection: Articulatory Analysismentioning
confidence: 99%
“…Previous findings on Dominican Spanish have reported that the aspirated variant [h] is almost non-existent, and that the deleted one is, by far, the most frequent one in adult speech (see Bullock et al 2014;Terrell 1986). While aspiration of /s/ was attested in the 1920s and 1930s (Henríquez-Ureña 1940), today, deletion is well advanced, especially among younger speakers (Jiménez Sabater 1975).…”
mentioning
confidence: 99%
“…noun, determiner, adjective), phonological context (e.g. following sound), gender, SES, and speech style (Bullock et al, 2014;Cepeda, 1995;Lipski, 1994;Miller, 2013;Miller & Cardenas, 2020;Miller & Schmitt, 2012;Poplack, 1980), and Spanish /s/ lenition is prevalent in child-directed speech (Miller, 2007(Miller, , 2013Miller & Cardenas, 2020). When the plural marker /-s/ is omitted, the plural noun may be semantically ambiguous as illustrated for bold forms in (5).…”
Section: Processing In the Context Of Variable Inputmentioning
confidence: 99%
“…In the same vein, apparent cases of hypercorrection may in fact be or have become functionally constrained (e.g. Labov & Harris 1986: 13-17; Bullock et al 2014). 8 At that point, their occurrence no longer depends on automatic substitution of a vernacular form for a more prestigious form.…”
Section: Hypercorrectionmentioning
confidence: 99%
“…Although hypercorrection relies on automated paradigmatic relations, its output may always go on to lead a life of its own, as a stored chunk (see Section 4.4). In the same vein, apparent cases of hypercorrection may in fact be or have become functionally constrained (e.g., Bullock, Toribio, & Amengual, 2014;Labov & Harris, 1986, pp. 13-17).…”
Section: Hypercorrectionmentioning
confidence: 99%